PENGARUH KECERDASAN EMOSIONAL DAN KOMPENSASI TERHADAP KOMITMEN ORGANISASI PEGAWAI SEKOLAH BINA BHAKTI KUBU - Juliahir Barata (Jurnal Ekonomi Integra, 2020)
Background the research is to various assessment empirical and the phenomenon of emotional intelligence and compensation and their influence on commitment organization employees in bina bhakti school, kubu raya. Methods used in this research is quantitative model with a multiple linear regression. The subject of this research is school office bina bhakti kubu raya 31 which consisted of people. Data collection techniques is using a questioner, observation and interview. Collected data has been will analyzed by the statistics to determine the level of influence between variables free on variables bound. Based on the regression, the can be made conclusion as follows: 1) There are significant influence between variables emotional intelligence to commitment on organization of employees in Bina bhakti kubu raya as much as 98,52%; 2) There are significant influence between variables compensation to commitment on organization of employees in Bina bhakti kubu raya as much as 98,96%; 3) There are significant influence between variables emotional intelligence and  compensation to commitment on organization of employees in Bina bhakti kubu raya as much as 99,20%.